Freeze-Dried Food in the Diet of Temporary Residents of the Far North - Evgeniy I. Titov; Irina S. Krasnova; Vera I. Ganina; Elena G. Semenova (Техника и технология пищевых производств)
Introduction. The Russian Arctic, also called the Far North, attracts a lot of people who work on a fly-in fly-out basis. These temporary residents experience the negative impact of the harsh climate and suffer from unvaried diets and poor ration. Freeze-dried products might be the optimal solution to this problem. The research objective was to find a rationale for the use of freeze-dried long-storage products in the diets of temporary residents in regions with harsh climatic conditions. Study objects and methods. The research featured scientific publications on two topics: 1) nutrition and diet of shift workers in the Far North, 2) development of freeze-dried products for long-term storage in extreme conditions. Results and discussion. Shift workers consume a lot of fats and carbohydrates, while their diet lacks complete proteins, vitamins, minerals, dairy products, and fresh fruits and vegetables. Taking into consideration the high content of sugar and confectionery, the diet ruins the health of the temporary residents and causes alimentary chronic non-infectious diseases. A healthy diet for the Russian Arctic should correspond to the metabolic profile typical of people in chronic environment stress and be complete both quantitatively and qualitatively. Important food products are difficult to deliver to the Far North. As a result, they are microbiologically and chemically contaminated. Therefore, the region needs high-quality functional products with prolonged shelf life. Conclusion. Freeze-dried fermented milk products, fruits, and vegetables can help temporary residents of the Far North to maintain their usual food patterns. Freeze-dried foods have a long shelf life in unregulated temperature conditions, which can solve the issue of food supply even to the most remote settlements.